2022
DOI: 10.1039/d2ra02351b
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-based drug delivery systems and their therapeutic applications

Abstract: In the past few decades, scientists have actively worked on developing effective drug delivery systems (DDSs) as means to control life-threatening diseases and challenging illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 111 publications
0
16
0
Order By: Relevance
“…In addition, the functional characteristics of exosomes is depending on their origin (Lee et al 2022 ). The use of tumor-derived exosomes to deliver therapeutic agents such as chemotherapeutic or anti-cancer agents or to develop vaccines for immunotherapy can be interesting from different aspects.…”
Section: Current Challenges In Exosome-based Therapiesmentioning
confidence: 99%
“…In addition, the functional characteristics of exosomes is depending on their origin (Lee et al 2022 ). The use of tumor-derived exosomes to deliver therapeutic agents such as chemotherapeutic or anti-cancer agents or to develop vaccines for immunotherapy can be interesting from different aspects.…”
Section: Current Challenges In Exosome-based Therapiesmentioning
confidence: 99%
“…Physical loading methods including electroporation, ultrasound and extrusion have also been widely applied to load drugs ( 125 ). Electroporation is a strategy that drugs are instantaneously loaded into Exos under an electrical impulse ( 126 ).…”
Section: Exos As Drug Delivery Carrier For Cancer Immunotherapymentioning
confidence: 99%
“…To expand on exosomes, exosomes as a cell-derived nano-delivery vehicle have received increasing focus owing to their diverse origins and a range of functionality. 78 For example, Unciti-Broceta and co-workers designed a mild chemical approach to in situ directly synthesize Pd nanosheets inside A549 cancer cell-derived exosomes (Pd-Exo A549 ) through using carbon monoxide (CO) as a gaseous reductant, while not affecting the integrity and functionality of exosomes. A series of experimental results revealed that the Pd nanosheets were successfully synthesized within the exosomes with an average Pd content of 0.64 ÎŒg per ÎŒg of Pd-Exo A549 protein, and the membrane proteins of the exosomes remained intact.…”
Section: The Development Of Tmc-based Bioorthogonal Nanozymesmentioning
confidence: 99%